Development and validation of a scale to measure the simulation-based learning outcomes in teacher education - Levin, Orna; Frei-Landau, Rivi; Goldberg, Chen (Frontiers in Education, 2023)
Simulation-based learning (SBL) is gradually being integrated into the field of teacher education. However, beyond specific content acquisition, comprehensive knowledge of SBL outcomes is limited. This research aimed to systematically develop a scale to measure SBL outcomes in teacher education, using a mixed-methods sequential exploratory design. Data were collected in two phases: a qualitative (N=518) phase followed by a quantitative (N=370) phase. Data analysis revealed three types of measurable SBL outcomes: communication skills, emotional self-awareness, and collaborative-learning-related insights. The study provides a theoretical conceptualization of SBL's multifaceted learning outcomes in the field of teacher education. These findings allow for a better understanding of the observers’ role in SBL, suggesting that enacting the simulation is not inherently more emotionally demanding and, consequently, participants in both roles are apt to benefit equally from the experiential learning afforded by the SBL process. Theoretical and practical implications of using SBL in the teacher-education field are discussed.